If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + 7)(5x + 3) = 0 Reorder the terms: (7 + 7x)(5x + 3) = 0 Reorder the terms: (7 + 7x)(3 + 5x) = 0 Multiply (7 + 7x) * (3 + 5x) (7(3 + 5x) + 7x * (3 + 5x)) = 0 ((3 * 7 + 5x * 7) + 7x * (3 + 5x)) = 0 ((21 + 35x) + 7x * (3 + 5x)) = 0 (21 + 35x + (3 * 7x + 5x * 7x)) = 0 (21 + 35x + (21x + 35x2)) = 0 Combine like terms: 35x + 21x = 56x (21 + 56x + 35x2) = 0 Solving 21 + 56x + 35x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '7'. 7(3 + 8x + 5x2) = 0 Factor a trinomial. 7((1 + x)(3 + 5x)) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Subproblem 2
Set the factor '(3 + 5x)' equal to zero and attempt to solve: Simplifying 3 + 5x = 0 Solving 3 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 5x = 0 + -3 5x = 0 + -3 Combine like terms: 0 + -3 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6Solution
x = {-1, -0.6}
| (2/3)x-3=(5/6)x | | -2x-(-4)-4x=3x+3-9x | | .20x+.35(70)=39.5 | | -3m+12/24-4m-8/8-m+2/16=0 | | 4n-3-8n+15=0 | | (11x+8)(2x+5)= | | 5(x)-6/3= | | 15=-3(c+9) | | n-39=-11 | | (3x-40)+(2x+15)=90 | | 2y+18=2 | | -2v+6v=4 | | 5x+27=10x+2 | | 2s-5=-20 | | X-1+5x=32 | | -8*14=-2(4x-7) | | 10x(11x^2+5x+4)= | | 50-3a=75 | | 4x+y-5h=10y+uforx | | 2(4x-1)=9x-x | | L=5/9(f-32) | | 1.25y-20.5=0.5y-11.5 | | 8x+6x=96 | | 6+7q=9+6q | | (6x)(11x+9)= | | 4(x-4)=2(x+3) | | 9(c-6)=8(c-9) | | 1/2(3x-4)=3/4(x-6)+1 | | 5x-(9)=7x+6-2x | | -15c+3=-7+5c | | 5x+6=8x-9 | | 5x+31=-53+9x |